CANDLE syndrome – a narrative review - Aleksandra Snopkowska; Joanna Gołda; Julia Mężyk; Piotr Gacka; Marcin Dołęga (Pediatria Polska)
CANDLE syndrome (chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature) is a rare autoinflammatory disorder beginning in early childhood. This narrative review provides an extensive overview of CANDLE syndrome, including its epidemiology, aetiology, clinical manifestations, diagnostic challenges, and current treatment options. The syndrome is associated with gene mutations encoding proteasome or immunoproteasome subunits, particularly PSMB8, contributing to disrupted proteostasis and aberrant type 1 interferon production. The diagnostic criteria remain undefined, necessitating a multidisciplinary approach for accurate diagnosis and management. Despite therapeutic complexities, recent advancements in genetic testing and targeted therapies, notably Janus kinase inhibitors, offer promising avenues for improved patient outcomes. Further research and clinical trials are imperative to enhance understanding and optimise treatment strategies for this rare and debilitating condition.